Perancangan Aplikasi Project Managament Berbasis Web di Bidang Pembangunan dan Aktivasi dengan Model Agile Scrum - Nurhabibah, Salma Dewi; Danoesoebroto, Ardityo (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2024)
PT. Indonesia Comnets Plus (ICON PLUS) SBU West Java Region in the Development and Activation Division requires an application that can improve efficiency in data processing because previous data was processed manually and not integrated. The purpose of this study is to design and implement a web-based project management application using the Laravel framework and using the agile scrum writing method. The stages carried out from the beginning are planning the project (Project Planning), then creating a product backlog, then doing sprint planning, doing sprints, doing daily scrums, doing sprint reviews, which design is implemented. After the system is built, testing is carried out on the system using Black Box Testing and User Acceptance Testing (UAT). The results of the design of the web-based project management application in the development and activation division produce 4 user actors, namely Super Admin, Staff, Maintenance, and Technicians. The implementation of this system utilizes information technology by optimizing management to manage data efficiently, access information quickly, and facilitate communication between parties involved in managing the web-based project management application in the development and activation division. Keywords: project management, agile scrum method, data processing efficiency